The role of neuropeptide Y in the pathophysiology of atherosclerotic cardiovascular disease. (1st October 2016) - Zhu, Ping; Sun, Weiwei; Zhang, Chenliang; Song, Zhiyuan; Lin, Shu
Abstract: With average life expectancy rising greatly, the incidence rate of arteriosclerotic cardiovascular disease (ASCVD) has significantly increased. The heart disease has now become the number one killer that threatens the global population health, the second is stroke. It will be of great significance to investigate the underlying pathophysiological mechanisms of ASCVD in order to promote effective prevention and treatment. The neuropeptide Y (NPY) has now been discovered for more than thirty years and is widely distributed in the central nervous system (CNS) and peripheral tissues. By combining with certain receptors, NPY performs a variety of physiological functions, including the regulation of food intake, cardiovascular effects, development, hormonal secretion, sexual behavior, biological rhythms, temperature and emotion. In ASCVD, increased peripheral NPY was involved in the pathophysiological process of atherosclerosis through affecting the vascular endothelial dysfunction, the formation of foam cells, the proliferation of vascular smooth muscle cells, the local inflammatory response of plaques and the activation and aggregation of platelets. Via central and/or the peripheral nervous system, increased NPY was associated with dyslipidemia, hypertension, obesity, diabetes, impaired glucose tolerance, and smoking which are all risk factors for ASCVD. In this review, we summarize the role of neuropeptide Y in the development of atherosclerotic cardiovascular disease. Highlights: The pathophysiological mechanisms underlying ASCVD remains unclear. Hypothesize that NPY is closely related to ASCVD Specify the role of NPY in blood lipid metabolism, glucose metabolism and blood pressure regulation Discuss the potential risk predictor and therapeutic target of NPY in treating the ASCVD